2009
DOI: 10.1108/17554190911005309
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of advertising and distribution expenditure on Tobin's Q

Abstract: PurposeThe purpose of this paper is to understand the impact of components of marketing expenditures, i.e. advertising and distribution expenditures on intangible value of firm (measured in terms of Tobin's Q). The relationship is studied in the context of branding approaches (corporate and house of brands) that various firms follow.Design/methodology/approachThe data are collected from databases of Centre for Monitoring Indian Economy (CMIE) and from the web site of National Stock Exchange. Time series regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 21 publications
3
20
0
Order By: Relevance
“…Shareholder value comprises both the tangible and intangible value of the firm. In recent times, intangible assets are becoming more salient and significant due to the increased emphasis on value attributed to the firm (Sahay and Pillai, 2009). Rao et al (2004) measured the impact of three different branding strategies (corporate branding, mixed branding and house-of-brands) on Tobin's Q, a measure of intangible value of the firm.…”
Section: Branding Strategy and Returns To Celebrity Endorsementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shareholder value comprises both the tangible and intangible value of the firm. In recent times, intangible assets are becoming more salient and significant due to the increased emphasis on value attributed to the firm (Sahay and Pillai, 2009). Rao et al (2004) measured the impact of three different branding strategies (corporate branding, mixed branding and house-of-brands) on Tobin's Q, a measure of intangible value of the firm.…”
Section: Branding Strategy and Returns To Celebrity Endorsementsmentioning
confidence: 99%
“…Chaiken, 1979;Langner and Eisend, 2011;Liu and Brock, 2011;McGuire, 1985), the effect of firm characteristics, especially the effect of branding strategy has not been examined. Prior research has revealed that branding strategy may moderate the impact of advertising expenditure on the intangible value of the firm (Rao et al, 2004;Sahay and Pillai, 2009). Hence, the effectiveness of celebrity endorsements (which are likely to form a significant proportion of a firm's advertising expense) may also depend on the branding strategy adopted by a firm.…”
Section: Introductionmentioning
confidence: 99%
“…The market capitalisation and intangible value is related, so a high value of Tobin's Q would show a higher value of the intangibles (Sahay & Pillai, 2009). The ratio is a forward-looking measure, indicating market-based views of investor expectations of the firm's future profit potential (Sahay & Pillai, 2009). Stewart (1997) specified that Tobin's Q is not intended to be a measure of IC but it can be a good indicator of IC.…”
Section: Tobin's Qmentioning
confidence: 99%
“…In their study, Luo and Jong (2012: 606) have indicated that advertising expenses both directly and indirectly affect sales and financial values of companies. In this regard, Sahay and Pillai (2009: 77) found that advertising expenses positively affect the market value of companies. Furthermore, efficiency of marketing communications has also a positive effect on the market value of a company (Luo and Jong, 2012: 605).…”
Section: Importance Of Advertising For Companies and Effect Of Advertising Expenses On Value Of Companymentioning
confidence: 99%
“…In this regard, by the means of forming a main research topic for this paper, it can be claimed that both the advertising expenses and the R & D expenses may affect the market value of a company and its performance as well. In studies conducted on this subject (Luo and Jong, 2012: 606;Joshi and Hanssens, 2010;Chauvin and Hirschey, 1993;Andras and Srinivasan, 2003;Sahay and Pillai, 2009;Peterson and Jeong, 2010;Hirschey and Weygandt 1985: 327), it has seen that either advertising or R & D expenses may have an effect on company performance.…”
Section: Introductionmentioning
confidence: 99%